Prosperity in progress: a new look at archetypes of successful community development - Hampton, Midas; O’Hara, Sabine (Frontiers in Sustainable Cities, 2024)
This study navigates the terrain of community development in metropolitan areas across the United States (US), spotlighting the interplay between stakeholder engagement, development success, and distinct types of community development characteristics. While urban centers in US cities experienced disinvestment and urban flight for more than 5 decades, they now experience renewed interest amidst the complexities of rampant urbanization. Gentrification and displacement are some of the critical consequences of urban re-development, which warrants the exploration of the success metrics that turn disinvested communities into thriving ones. Methodologically, archetype analysis is employed to examine 73 case studies reported by the United States Department of Housing & Urban Development (HUD) as examples of successful development. The case studies span 37 US states and 67 cities. The analysis utilizes the Distressed Communities Index (DCI) as a supporting metric and offers an intermediate level of abstraction between a case-by-case analysis of successful development strategies and a generalized approach that assumes that one strategy fits all. Instead, the analysis identifies four distinct types of successful community development archetypes based on five relevant characteristics that emerged from our analysis: (1) public investments, (2) private investment (3) development plans, (4) stakeholder engagement, and (5) the DCI. The four identified archetypes represent unique Community Development Success pathways with specific development characteristics. Understanding the diversity reflected in these distinct archetypes is crucial for policymakers and stakeholders seeking to address the specific needs and challenges of each development success type. This can inform more targeted policy initiatives for fostering prosperity and vitality in diverse communities across the US and beyond.